Growth Analysis of Seeds Oil Palm on Stage Pre Nursery and Main Nursery at PT. Socfindo - Purnama, Hari; Afrillah, Muhammad (Green Publisher, 2022)
Oil palm (Elaeis Guineensis Jagc.) is an oil palm plant belonging to the palm group which is an annual plant, oil palm is also a source of non-oil and gas foreign exchange for Indonesia. This research activity was carried out at PT. Socfindo Kebun seunagan, Nagan Raya, West Sumatra from 18 November 2021 to 16 December 2021. Research activities are specifically at learning and improving technical and managerial skills. The data obtained are primary data (direct) and secondary data (indirect). Primary data is data that the author directly observed during his internship at PT. Socfindo, in the form of plant height, stem diameter, and number of leaves. Direct observations to determine technical activities in the field and compared to standards, as well as direct discussions with workers and staff about oil palm nurseries. Secondary data obtained from daily reports, monthly reports and plant archives, secondary data includes climate, fertilization, organizational structure and matters related to labor. Observations on the vegetative growth of oil palm seedlings are expected to achieve appropriate growth. The purpose of this observation activity is to improve understanding, and technical skills, as well as to analyze oil palm nursery activities at the Pre-nursery and Main nursery stages at PT. Socfindo Seunagan Gardens.